Site-directed mutagenesis of beta-lactamase I: role of Glu-166. - Leung, Y; Robinson, C; Aplin, RT; Waley, S (1994)
Two Glu-166 mutants of beta-lactamase I from Bacillus cereus 569/H were constructed: one with a lengthened side chain (E166Cmc, the S-carboxymethylcysteine mutant) and the other with the side chain shortened and made non-polar (E166A). Their kinetic properties were studied and compared with those of the wild-type and the E166D mutant (with a shortened side chain) previously made by Gibson, Christensen and Waley (1990) (Biochem. J. 272, 613-619). Surprisingly, with good penicillin substrates, Km, kcat. and kcat./Km of the two conservative mutants (E166Cmc and E166D) are similar to those of the non-conservative mutant E166A. Their kcat. values are 3000-fold lower than that of the wild-type enzyme, showing that Glu-166 is a very important residue. The acylenzyme intermediate of E166A and a good substrate, penicillin V, was trapped by acid-quench and observed by electrospray ionization mass spectrometry, suggesting that Glu-166 is more important in catalysing the deacylation step than the acylation step. The beta-lactamase I E166A mutant is about 200-fold more active than the Bacillus licheniformis E166A mutant with nitrocefin or 6 beta-furylacryloyl-amidopenicillanic acid as substrate. This suggested that other groups in the active site of the beta-lactamase I mutant may activate the catalytic water molecule for deacylation.